Investigating silicon nanoparticles modified sandwich polymer composites for enhanced mechanical performance - Mani, Megavannan; M, Thiyagu; Krishnan, Pradeep Kumar (Advances in materials and processing technologies (Abingdon, England), 2025)
This study investigates the morphology and mechanical behaviour of a bidirectional interply hybrid sandwich polymer composite panel with the addition of silica nanoparticles (SiNPs). The investigation assesses the enhanced performance of sandwich polymer composite panels, focusing on their ability to withstand compression, Euler's buckling axial load-bearing capacity, and surface roughness when subjected to low-velocity impact events that are barely perceptible for aircraft, automobile, and wind turbines. The composite panel was constructed using interply bidirectional Kevlar, carbon, and glass fibers, an epoxy matrix, and polyurethane (PUR) foam, with the incorporation of four different weight percentages of silica nanoparticles (0%, 2%, and 4% of SiNPs). The sandwich composite panel was fabricated using the hand lay-up technique, following a novel quasi-static stacking sequence method (0 1 K /0 1 C /0 1 G /PUR/0 1 G /0 1 C /0 1 K ). Among these composite panels, the addition of 4 wt.% silicon nanoparticles exhibited the highest strength and axial load-carrying capacity compared to the other sandwich composite panels (0 wt.% and 2 wt.%). The mechanical characterisation results showed maximum compressive strengths of ca. 3 MPa, ca. 5 MPa, ca. 10 MPa, and ca. 8 MPa for the 0 wt.%, 2 wt.%, 4 wt.% and 6 wt.% of silica nanoparticles-added composite panels, respectively.